DUKUNGAN KELUARGA DALAM KEGIATAN KELOMPOK PERAWATAN DIRI (KPD) PENDERITA KUSTA DI KABUPATEN BREBES - Devi Ayu Susilowati; Widya Hary Cahyati (Dian Nuswantoro Semarang, 2016)
Leprosy is a disease that poses a complex problem, both in terms of medical disability due cause. One way to prevent those with self-care disability. Activities of Self-Care Group (KPD) in the Brebes district only runs 3 months in November-December of 2013 so that researchers and health centers will re-enable this activity. The purpose of this study was to determine whether there is a relationship between family support with the participation of leprosy patients in KPD in Brebes district. This research is an analytic survey with cross sectional approach. The population is all leprosy patients from 4 health centers with the highest number of people in the Brebes district health centers Jatirokeh, Jatibarang, Wanasari, and Sitanggal. The sampling technique using total sampling are 32 people in 4 health centers. Analysis using chi square test. The results of the chi square test the relationship between family support with the participation of leprosy patients in KPD Brebes with p value 0.044 (<0.05). Advice for the head of the health centers and leprosy program officer that regular monitoring meetings whenever KPD and socialization, especially in rural areas, the lepers are seeking to continue attend regular meetings in the activities of the KPD.Keywords: Leprosy; Self-Care Group; Family support; Participation